Effects of lagundi (Vitex negundo L.) crude extracts on some reproductive parameters of adult male albino rats - Ocampo, Pablo P. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1992)
The effects of Vitex negundo L. crude extract on some reproductive param-eters (viz: sperm morphology, sperm production, motility and histology) were evaluated in male albino rats. Crude hexane extracts of the test material were administered to the animals by gavage technique. V. negundo was found to cause significant decrease in sperm motility and sperm counts; and rats treated with higher and moderate doses exhibited significantly higher testicular weights. Body weights and epididymal weights, however, were not affected. There were no apparent effects on the sperm morphology among treated rats. Histological evaluation of the testes revealed that the test extract can cause marked interstitial fluid accumulation and spermatogenic irregularities. Testicular damage in one of the animals under the high dose treatment level revealed severe degeneration of the semeniferous tubules and interstitial fluid accumulations.